Difficulties of English Study Program Students to Answer the Reading Comprehension TOEFL - Fauzia, Wanna Imra; Kemal, Edwar; Syafar, Dian Noviani (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2024)
TOEFL is one of the tests where all students are required to take the TOEFL test to test their abilities and measure their English language skills as a process of academic requirements that have been determined by each individual university. TOEFL is divided into three types of questions: students are asked to listening to what the speaker says to measure listening skills, reading texts where the student is asked to understand the reading text that has been questioned by the writer, written structure questions grammar. This study discusses what difficulties English language education students have in answering the reading comprehension TOEFL test. This research uses Quantitative method. The data was collected using the total sampling technique, then the sample population that the researchers took was 68 English education students in 2021. Furthermore, the data were analyzed using questionnaires and interviews. The results explained that TOEFL is a test to measure the English language skills of students, Non native speakers. From the internal context, it was found that students' difficulties in answering reading toefl were five difficulties such as difficulties in determining the main idea, implied detail question, unstated detailed, stated detail question and vocabulary question. From the external context, it is found that students are lazy to read because the text is too long.